Corporate sustainability disclosure on social media and its difference from sustainability reports:Evidence from the energy sector - Zhong, Ma; Wang, Mingyue (Frontiers in Environmental Science, 2023)
This paper aims to investigate the sustainability information that energy firms disclose on social media and the connection between this information and that disclosed in traditional sustainability reports. Based on stakeholder theory, we use a sample of Chinese listed energy firms in 2020 and refer to GRI G4 guidelines to conduct content analysis on their 17,451 tweets from the WeChat platform and 53 sustainability reports. The analysis results show the following: (1) both the sustainability disclosures of Chinese energy firms on social media and sustainability reports focus on investor and employee dimensions. Among them, the average proportion of investor dimension disclosure to total disclosure is 31.92% and 27.22% on social media and sustainability reports, respectively, and the average proportion of employee dimension disclosure is 35.19% and 17.92%, respectively. However, the two channels show a large difference in the environmental and governmental dimensions. The average proportion of environmental disclosure in sustainability reports is 13.44%, while on social media it is only 2.01%. Governmental disclosure in sustainability reports is 8.24% and as high as 20.43% on social media. (2) Chinese energy firms prefer to provide supplementary information on social media. For example, using the investor dimension as an example, the average proportion of non-GRI information on social media is 74.20%, while that of the sustainability report is only 39.30%.